Case Report: Mitochondrial Encephalomyopathy Presents as Epilepsy, Ataxia, and Dystonia With a Rare Mutation in MT-TW - Wang, Shuang; Miao, Jing; Feng, Jiachun (Frontiers in Neurology, 2021)
Mitochondrial diseases are a group of common inherited disorders caused by mutations in nuclear DNA or mitochondrial DNA (mtDNA); the clinical phenotype of diseases caused by mutant mtDNA is challenging owing to heteroplasmy of mtDNA and may delay diagnosis and treatment. Herein, we report the case of an adult male who slowly developed epilepsy, ataxia, dystonia, impaired cognition, and hearing impairment over 14 years in the absence of clinical myopathy. His lactate level was normal. Brain computed tomography showed calcifications of the bilateral basal ganglia, thalamus, and cerebellar dentate nuclei. Magnetic resonance imaging revealed multiple lesions in the bilateral internal capsule and periventricular areas, which were hypointense on T1-weighted images and hyperintense on T2-weighted images. The first blood genetic test result was negative. Two years later, a muscle biopsy was performed. Succinate dehydrogenase (SDH) staining showed several ragged blue fibers and atypical strongly SDH-reactive vessels. Cytochrome C oxidase (COX) staining revealed abundant COX-deficient fibers. mtDNA testing of blood and muscle revealed a rare m.5549G>A mutation in the MT-TW gene. It was heteroplasmic, with 5.4% mutant mtDNA in the blood and 61.5% in the muscle. The patient was diagnosed with mitochondrial encephalomyopathy and treated with levetiracetam instead of valproate to reduce possible mitochondrial toxicity. After receiving anti-epileptic drugs and mitochondrial supplements, the patient remained clinically stable. For mitochondrial disease, when mutant mtDNA is not detected in blood, muscle biopsy should be performed in routine analysis, and it should be genetically tested, even if there are no manifestations of myopathy.